Historical Pocket Book Application As an Alternative Media of History Learning - Utomo , Cahyo Budi; Lusianto , Junaidi Fery (KnE Social Sciences, 2019)
The use of technology will never be separated from aspects of human life. Even now in the world of learning is required to utilize information technology as a support. Like wise with history learning, it is appropriate to adopt various existing information technologies to support history learning. Historical pocketbook based on Android is one of the alternative media innovations in learning history. The use of this application can support effectiveness and reduce the students’ view of history learning which has always been negative. Keywords: application; media; learning; historical pocketbook